Loan pricing, financial intermediation and Loan costs in Uganda’s deposit taking Institutions - Kamukama, Nixon; Natamba, Bazinzi (African Journal of Accounting, Economics, Finance and Banking Research, 2011)
The paper examined individual contribution of loan pricing and financial intermediation to loan costs. Its purpose was to explore the extent to which predictor variables (loan pricing and financial intermediation) explain loan costs in Ugandan Microfinance Deposit Taking Institutions (MDIs). Besides, the study assessed the extent to which MDIs have implemented or enforced the prudential regulations set by Bank of Uganda. Hierarchical regression was used because of its capacity to indicate precisely what happens to the model as different predictor variables are introduced. This study established that the two predictor variables are strong predictors of loan costs and they account up to 32 percent of variance in loan costs. More so, prudential requirements implementation is still desired since they are not properly implemented. Findings can help management to intensify initiatives to encourage greater understanding and acceptance of the concept of loan pricing and financial intermediation so that that competitive loan costs can be set and benefit all stakeholders in the industry
Keywords: Loan Pricing; Savings Intermediation; Microfinance Deposit Taking Institutions (MDIs); Loan Costs